Engineering Specificity and Function of Therapeutic Regulatory T Cells - McGovern, Jenny L.; Wright, Graham P.; Stauss, Hans J. (Frontiers in Immunology, 2017)
Adoptive therapy with polyclonal regulatory T cells (Tregs) has shown efficacy in suppressing detrimental immune responses in experimental models of autoimmunity and transplantation. The lack of specificity is a potential limitation of Treg therapy, as studies in mice have demonstrated that specificity can enhance the therapeutic potency of Treg. We will discuss that vectors encoding T cell receptors or chimeric antigen receptors provide an efficient gene-transfer platform to reliably produce Tregs of defined antigen specificity, thus overcoming the considerable difficulties of isolating low-frequency, antigen-specific cells that may be present in the natural Treg repertoire. The recent observations that Tregs can polarize into distinct lineages similar to the Th1, Th2, and Th17 subsets described for conventional T helper cells raise the possibility that Th1-, Th2-, and Th17-driven pathology may require matching Treg subsets for optimal therapeutic efficacy. In the future, genetic engineering may serve not only to enforce FoxP3 expression and a stable Treg phenotype but it may also enable the expression of particular transcription factors that drive differentiation into defined Treg subsets. Together, established and recently developed gene transfer and editing tools provide exciting opportunities to produce tailor-made antigen-specific Treg products with defined functional activities.